Burden of mortality and its predictors among TB-HIV co-infected patients in Ethiopia: Systematic review and meta-analysis. - Amare Kassaw; Demewoz Kefale; Tigabu Munye Aytenew; Molla Azmeraw; Muluken Chanie Agimas; Shegaw Zeleke; Mastewal Ayehu Sinshaw; Nigatu Dessalegn; Worku Necho Asferie (PLoS ONE)
Background Human immunodeficiency virus (HIV) and tuberculosis (TB) are still the two major deadly pandemics globally, causes 167,000 deaths in 2022. The two lethal combinations pose a substantial challenge to public health, especially in areas with high burden of both diseases such as Sub-Saharan Africa including Ethiopia. However, there is no study that showed national figure on mortality of TB/HIV co-infected patients. Hence, this review intended to provide pooled mortality rate and its predictors among patients co- infected with twin pandemics. Methods Using reputable electronic data bases, primary studies were searched from January 25 to February 5, 2024. The review included papers published in English language conducted between 2004 and 2024. Heterogeneity between included studies was evaluated using Cochrane Q-test and the I2 statistics. Sub-group analysis was done to mitigate significant heterogeneity. Sensitivity analysis was also done to evaluate the effect of single studies on pooled estimated result. Results In this systematic review and meta-analysis a total of 5,210 study participants were included from 15 primary studies. The review disclosed that the pooled proportion and incidence of mortality were 18.73% (95% CI: 15.92-20.83) and 4.94 (95% CI: 2.98-6.89) respectively. Being bedridden and ambulatory functional status, poor ART adherence, CD4 count below the threshold (<200 cells/mm3), advanced WHO clinical staging, not provision of cotrimoxazole and isoniazid preventing therapy, anemia and extra pulmonary TB were significant predictors of mortality. Conclusion and recommendations The analyzed data of this systematic review and meta-analysis depicted that the national pooled proportion and incidence of mortality among TB-HIV co-infected patients were considered to be still high. The authors strongly recommended scale up and continuous provision of cotrimoxazole and isoniazid preventive therapy. In addition, early identification and treatment of anemia will greatly halt the high burden of mortality. Generally, to reduce mortality and improve survival, a collaborative effort is mandatory to emphasize close follow up of patients with identified predictors.